Isolation and Antimicrobial Characterization of Aerobic Pathogenic Bacteria from Egg Shell and Egg Contents in Table Eggs in Erbil - Ahmed I. Ahmed (Journal of Global Pharma Technology, 2019)
Contaminated eggs are the major reservoirs for many foodborne pathogens and their ability to produce toxins causing diseases or even death in human. One of the essential quality characteristics of eggs is hygienic quality, lack of good hygienic practices, which may lead to loss the quality and deterioration of eggs. This study was focused on fresh chicken eggs to determine the prevalence and level of contamination in process as well as risk of antibacterial resistance of isolated bacteria. The level of contamination of table eggs with pathogenic bacteria and the antimicrobial resistance (AMR) were examined. Total numbers of 72 fresh chicken eggs were collected from eight flocks including conveyer belt and storage eggs from two large scale poultry layer farms in Erbil. The total bacteria on its eggshell was counted, bacterial loads were ranged between 5.174-5.854 log cfu/ eggshell. Bacteria isolated colonies subculture on Macconkey agar and gram negative baccilli were inoculated on VITEK® 2 ID-GNB (identification-Gram-negative bacilli) and antimicrobial susceptibility testing (AST)-GN69 cards. The bacterial pathogenic contamination ratio was 22.2% Staphylococcus and 22.2% enterobacteriaceae mostly (E-coli 11%). Whereas no bacteria were found in polls egg contents. The highest resistance rate was detected against Cefazolin, Amoicillin, Trimethoprim/ Sulfamethoxzol, Nitrofurantoin, Ciprofloxacin, Levofloxacin. The high sensitivity rate was recorded against Piperacillin/Tazobactam, Imipenem, Ertapenem, Gentamycin, Tobramycin, Cefipime, Cefitraxone. The results of this study conclude that the bacterial load on egg shells and contents were at the accepted level while the isolation of pathogenic bacteria due to lack of hygiene practice should be considered, also we suggest that the farmer must fumigate the fresh eggs with a good hygienic practice before marketing.